Thermodynamics of solid and liquid aluminium - E. I. Marukovich; V. Yu. Stetsenko; A. V. Stetsenko (Литьë и металлургия, 2021)
Based on thermodynamic calculations, it is shown that in the temperature range of 298–1273 K, heating and cooling of aluminum are thermodynamically equilibrium processes. When aluminum is heated, the molar volume energy of Gibbs decreases and the molar boundary energy of nanocrystals increases. When aluminum is cooled, the molar volume energy of Gibbs increases and the molar boundary energy of nanocrystals decreases. Liquid aluminum is a nanostructured system. Dendritic microcrystals are formed from nanocrystals. They play a large role in the processes of changing the structure of aluminum during its heating and cooling.